Pengaruh waktu pemanasan dan pengasaman terhadap kadar albumin ekstrak ikan gabus : The effect of long heating and aciditing time on albumin levels in snakehead fish extract - Yuniati, Renni; Nurtari, Rahma Yulia; Annaafi, Alviona Denti; Priguna, Tangkas Mukti; Anggita, Vinka Dwi; Kusumaningrum, Novi; Saraswati, Indah; Muslimin, Muslimin; Putra, Farmaditya Eka; Hardian, Hardian (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2024)
Snakehead fish, specifically the Channa striata species, are known to have an abundance of albumin. However, there is limited information available regarding alterations in the properties of snakehead fish extracts that have undergone high heat and acid treatment. This presents a compelling research area for further exploration and study. The aim of this study was to determine the optimal portion of the fish and to examine the effect of heating and acidification time on albumin concentration in snakehead fish. The method employed in this study involved heating samples at 70 °C for 0, 15, and 30 min and subjecting them to acidification at pH 1, 4, and 7. The extraction process was conducted using centrifugation at a speed of 6,000 rpm for 60 minutes, followed by absorbance measurement at a wavelength of 280 nm using a UV-Vis spectrophotometer to evaluate the properties of protein extracts.The relationship between albumin levels and protein levels is one of direct proportionality.According to recent studies, snakehead fish extract is a safe and effective topical treatment for skin conditions, with a pH level ranging from 4.5 to 6.5. Furthermore, snakehead meat is a rich source of albumin, containing approximately 22.4 mg of protein per 100 g. The absorbance exhibited a more substantial rise at a temperature of 70oC over a 15-minute period and in a highly acidic environment (pH 1.0). Snakehead fish protein extract is less stable and more susceptible to denaturation than standard bovine serum albumin (BSA).